Digital Empathy and Solidarity: Case Study of Netizen Responses to MSMEs in Crisis - Fitria Mumtazah; Araffi, Mayogi; Noor, Muhammad (Universitas Muhammadiyah Jember, 2025)
This study aims to understand how consumers respond to the crisis experienced by Micro, Small and Medium Enterprises (MSMEs) actors, especially in terms of customer engagement and loyalty. This study uses a qualitative approach with thematic narrative design and netnography strategy. Data were collected through documentation of comments on social media related to the closure of the “Mama Khas Banjar” business, an MSME that experienced a crisis due to legal issues. The results showed that the crisis led to emotional solidarity from customers, in the form of moral and spiritual support delivered publicly. Consumers are not only silent, but actively involved in defending business actors. In addition, criticism of disproportionate law enforcement also surfaced in online discussions. The findings also strengthen the perception that MSMEs are seen as pillars of the people's economy that must be protected, not punished. This research confirms that consumer loyalty can be formed not only because of service satisfaction, but also because of emotional attachment and human values. The findings are important for MSMEs, government, and researchers in understanding the dynamics of customer relationships during a crisis.